2008
DOI: 10.1371/journal.pone.0002636
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of Malaria Transmission Blocking Vaccine Candidates Pfs25 and Pvs25 Formulated with Montanide ISA 51

Abstract: BackgroundPfs25 and Pvs25, surface proteins of mosquito stage of the malaria parasites P. falciparum and P. vivax, respectively, are leading candidates for vaccines preventing malaria transmission by mosquitoes. This single blinded, dose escalating, controlled Phase 1 study assessed the safety and immunogenicity of recombinant Pfs25 and Pvs25 formulated with Montanide ISA 51, a water-in-oil emulsion.Methodology/Principal FindingsThe trial was conducted at The Johns Hopkins Center for Immunization Research, Was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
335
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(342 citation statements)
references
References 29 publications
3
335
4
Order By: Relevance
“…Our safety report on MISA as an adjuvant for Leishmania vaccine differs from other studies that have associated this adjuvant with adverse reactions including swelling and erythema at the injection site observed within a few days following vaccination (PIERCE et al, 2010). Other studies have reported occasional unacceptable local reactogenicity in vaccines containing montanides (WU et al, 2008). It is likely that adverse reactions observed following immunizations with vaccines containing MISA may be a result of the immunizing antigen.…”
Section: Discussioncontrasting
confidence: 57%
“…Our safety report on MISA as an adjuvant for Leishmania vaccine differs from other studies that have associated this adjuvant with adverse reactions including swelling and erythema at the injection site observed within a few days following vaccination (PIERCE et al, 2010). Other studies have reported occasional unacceptable local reactogenicity in vaccines containing montanides (WU et al, 2008). It is likely that adverse reactions observed following immunizations with vaccines containing MISA may be a result of the immunizing antigen.…”
Section: Discussioncontrasting
confidence: 57%
“…However, it should be noted that 2 controlled studies on ISA 51-adjuvanted vaccines in healthy subjects were terminated prematurely due to unacceptable AEs. 40,43 The study of Wu et al was stopped after the 2 reported cases of erythema nodosum, which was not observed from other ISA 51-adjuvanted vaccine studies. The trial by Graham et al was stopped after 4 cases of sterile abscess, which was also reported by one subject who had erythema nodosum in the trial of Wu et al and by subjects in 2 other uncontrolled therapeutic vaccine studies in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…None of the participants in the adjuvant control groups developed AEs above moderate. 43 The prophylactic vaccine trials performed by Atsmon et al, Herrera et al and Pialoux et al reported the number of AEs after each immunization 11,41,42 . For the trial of Pleguezuelos et al, only the number of systemic AEs that occurred after a single injection could be extracted.…”
Section: Controlled Studies With Healthy Subjectsmentioning
confidence: 99%
“…For Montanide ISA 51, though little to no reactogenicity has been reported in animal studies and in some human studies [41,50-52], other human studies have concluded that this adjuvant, with its current composition, might not be suitable for use in humans due to high reactogenicity [42,43]. …”
Section: Discussionmentioning
confidence: 99%